Dopamine transporter availability in clinically normal aging is associated with individual differences in white matter integrity. Issue 2 (6th November 2015) - Rieckmann, Anna; Hedden, Trey; Younger, Alayna P.; Sperling, Reisa A.; Johnson, Keith A.; Buckner, Randy L.
Abstract: Aging‐related differences in white matter integrity, the presence of amyloid plaques, and density of biomarkers indicative of dopamine functions can be detected and quantified with in vivo human imaging. The primary aim of the present study was to investigate whether these imaging‐based measures constitute independent imaging biomarkers in older adults, which would speak to the hypothesis that the aging brain is characterized by multiple independent neurobiological cascades. We assessed MRI‐based markers of white matter integrity and PET‐based marker of dopamine transporter density and amyloid deposition in the same set of 53 clinically normal individuals (age 65–87). A multiple regression analysis demonstrated that dopamine transporter availability is predicted by white matter integrity, which was detectable even after controlling for chronological age. Further post‐hoc exploration revealed that dopamine transporter availability was further associated with systolic blood pressure, mirroring the established association between cardiovascular health and white matter integrity. Dopamine transporter availability was not associated with the presence of amyloid burden. Neurobiological correlates of dopamine transporter measures in aging are therefore likely unrelated to Alzheimer's disease but are aligned with white matter integrity and cardiovascular risk. More generally, these results suggest that two common imaging markers of the aging brain that are typically investigated separately do not reflect independent neurobiological processes. Hum Brain Mapp 37:621–631, 2016 . ©2015 Wiley Periodicals, Inc.